Meeting report of the RNA Ontology Consortium January 8–9, 2011. Issue 2 (March 2011) - Birmingham, Amanda; Clemente, Jose; Desai, Narayan; Gilbert, Jack; Gonzalez, Antonio; Kyrpides, Nikos; Meyer, Folker; Nawrocki, Eric; Sterk, Peter; Stombaugh, Jesse; Weinberg, Zasha; Wendel, Doug; et al.
Abstract This report summarizes the proceedings of the structure mapping working group meeting of the RNA Ontology Consortium (ROC), held in Kona, Hawaii on January 8–9, 2011. The ROC hosted this workshop to facilitate collaborations among those researchers formalizing concepts in RNA, those developing RNA-related software, and those performing genome annotation and standardization. The workshop included three software presentations, extended round-table discussions, and the constitution of two new working groups, the first to address the need for better software integration and the second to discuss standardization and benchmarking of existing RNA annotation pipelines. These working groups have subsequently pursued concrete implementation of actions suggested during the discussion. Further information about the ROC and its activities can be found athttp://roc.bgsu.edu/ .